LEGAL IMPLICATIONS OF HUSBAND'S MARRIAGE DURING THE IDDAH PERIOD (LEGAL STATUS AND LEGAL CONSEQUENCES) - Ayu, Diyan Putri; Mu’awanah, Elfi; Naim, Ngainun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research discusses the legal implications of a husband's marriage during his wife's iddah period, which is debated in Islamic law and positive law in Indonesia. In Islam, the iddah period aims to ensure the cleanliness of a woman's womb and provide an opportunity for reconciliation for divorced couples. However, classical Islamic law does not explicitly prohibit a husband from remarrying while his ex-wife is still in the iddah period. On the other hand, Circular Letter of the Director General of Islamic Guidance of the Ministry of Religious Affairs No. P-005/DJ.III/HK.007/10/2021 stipulates that marriages performed during the iddah period cannot be registered, as an effort to prevent covert polygamy. This research uses a normative juridical method with a legislative and conceptual approach, analyzing regulations related to marriage during the iddah period from the perspective of the Qur'an, Hadith, Compilation of Islamic Law (KHI), and Marriage Law No.1 of 1974. The results show a gap between classical Islamic law and state regulations, where positive law sets administrative restrictions on the husband's marriage during the wife's iddah period to provide legal certainty. This policy has consequences for the legal status of the marriage and the rights of the couple, including the status of the children in the marriage. This research provides insight into the differences between Islamic law and state regulations in the context of iddah marriages and their juridical implications, which are important for academics, legal practitioners and the public.